Risk factors and causes of End stage renal failure in Tarhuna Dialysis Center - Munder Zaied; Hussein Salama; Maryam Bougraine; Nisren Abdallah; Ali Aljadi (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
End-stage renal failure (ESRF) occurs when a patient’s kidneys have failed completely and can no longer filter waste products or produce adequate amounts of urine. Diabetes and hypertension are two leading causes of ESRF. Other risk factors for developing ESRF include chronic kidney diseases, genetic predisposition, lifestyle habits, and environmental exposures. A cross-sectional study of patients receiving treatment at the Tarhuna Dialysis Center (Libya) was conducted from December 2024 through February 2025. Using a demographic questionnaire (age, gender, and lifestyle factors) to collect data, researchers obtained data from 124 subjects. The most frequently reported age range was 30-45 years (34%) and 46-60 years (34%) of participants in the study. In addition to identifying risk factors associated with ESRF development, lifestyle factors associated with ESRF were also examined by gender. It appears that the following risk factors play a significant role in the development of ESRF: hypertension (27%), congenital anomalies (23%), diabetes (20%). All other risk factors for ESRF are less common (i.e. medication use without a prescription (16%), recurrent urinary tract infections (13%), protein loss in the urine (13%), cardiovascular disease (12%), dehydration (6%), and pulmonary disease (3%), and genetic disorders (1.6%). Therefore, it is important to continue education efforts to encourage early detection and treatment of chronic kidney disease and its associated risk factors before they develop into ESRF. According to the findings, many individuals with ESRF were noted to have hypertension and that by controlling hypertension, harbored the potential to reduce kidney failure rates. Identifying the types of preventative public health initiatives or identifying other prevalent causes of kidney failure could potentially aid to reduce the incidence of ESRF in individuals in Tarhuna City.